Preparation of curcumin / nitric oxide / photo-thermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel

Through curcumin and copper ion chelation and sodium nitroprusside nanocoprecipitation technology, a nanodrug composite dynamic crosslinked hydrogel with curcumin/nitric oxide/photothermal synergistic antibacterial was prepared, which solved the single existing antibacterial materials. Functional and drug resistance issues have achieved efficient and coordinated antibacterial effects.

CN119488476AActive Publication Date: 2025-02-21QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411715824.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-21
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Most of the existing antibacterial materials have only a single function, and the antibacterial effect is not ideal. Traditional antibiotics may lead to drug resistance, making it difficult to effectively solve the problem of bacterial infection.

Method used

Nanoparticles were formed by chelating curcumin and copper ions, and coated with polydopamine shell. Nanopharmaceutical PNO with core-shell structure was prepared by combining sodium nitroprusside and sodium phytate nanoprecipitation. The nanopharmaceutical PNO was prepared by dynamic cross-linking hydrogels and nanopharmaceuticals. Combination to achieve the synergistic antibacterial effect of curcumin/nitric oxide/photothermal.

Benefits of technology

It improves the water solubility and bioavailability of curcumin, enhances the antibacterial performance, and significantly improves the killing effect of bacteria through the synergistic effect of photothermal and gas therapy, and has good biocompatibility and injectability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488476A_ABST
    Figure CN119488476A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a curcumin / nitric oxide / photo-thermal synergistic antibacterial nano-drug composite dynamic crosslinking hydrogel. The preparation method comprises the following steps: chelating copper salt and curcumin to form first nano-particles, and coating the first nano-particles with polydopamine to form a nano-drug PCur; sodium nitroprusside and sodium phytate are used as raw materials, and a nano coprecipitation method is adopted to prepare second nano particles; then, polydopamine is adopted for coating the second nano-particles, and the nano-drug PNO of a core-shell structure is prepared; the nano medicines Pcur and PNO are uniformly mixed with the carboxymethyl chitosan and the oxidized hyaluronic acid, so that the nano composite dynamic cross-linked hydrogel is formed. The nano composite hydrogel not only has remarkable antibacterial performance, but also has the obvious advantages of being high in antibacterial effect, good in biological safety, convenient to prepare, low in cost and the like, medicine, photo-thermal therapy and gas therapy are combined in one device at the same time, and bacteria can be synergistically and accurately killed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of antibacterial hydrogels, and particularly relates to the preparation of a curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Human health is a key link in achieving sustainable development. Bacterial infection is one of the major diseases facing humans and is the second leading cause of death worldwide after ischemic heart disease, posing a challenge to global public health. However, traditional treatments, such as inorganic antimicrobial agents, may produce severe systemic toxicity, while antibiotics may produce drug resistance. At the same time, most of these materials have only a single function and the antibacterial effect is not ideal. Therefore, with the increasing number of drug-resistant bacteria, it has become crucial to develop new antimicrobial therapies.

[0004] Curcumin is one of the most widely used natural synthetic drugs in the world. It is a pigment molecule with photosensitivity and has been proven to have anti-aging, food coloring, free radical scavenging, lipid-lowering, anti-inflammatory, antioxidant, antibacterial, and anti-cancer effects. Due to its poor water solubility, unstable structure, and poor bioavailability, direct application of curcumin is difficult to fully exert its ideal medicinal value.

[0005] Nitric oxide (NO) is a short-lived, naturally occurring reactive oxidative gas that has potent antimicrobial properties through oxidative stress and inactivation of lipid, protein, and DNA targets. NO has well-established antifungal, antiviral, and antiparasitic properties through similar cellular mechanisms while being non-cytotoxic to mammalian cells at specific antimicrobial dose levels. More importantly, there is currently no evidence to support the propensity of NO to induce bacterial resistance.

[0006] In recent years, photothermal therapy has been used to effectively eradicate bacteria and biofilms by generating hyperthermia due to its advantages of broad-spectrum and high-efficiency antibacterial activity, good controllability, non-invasiveness, and prevention of multidrug-resistant bacteria. Many inorganic materials (such as gold nanoparticles, graphene, carbon nanotubes, and transition metal disulfides) and organic materials (such as small molecule preparations such as indocyanine green (ICG) and IR-825, and polymers such as polypyrrole, polyaniline, and dopamine (PDA)) have been reported as PTT biomaterials. As a melanin analog that naturally exists in the human body, PDA has the advantages of simple synthesis methods, antioxidant properties, adhesion properties, and biocompatibility, and is the most widely used in PTT.

[0007] Hydrogels have a three-dimensional network structure that is physically and functionally comparable to the natural extracellular matrix, making them suitable for nutrient delivery, cell communication, and cell regeneration. Hydrogels also have the advantages of good moisture retention, good biocompatibility, and designable physical structure, and are widely used in wound dressings. More importantly, hydrogels are also the best drug carriers, and by introducing structures that respond to different conditions (pH, ROS, glucose, etc.), smart drug release can be achieved. In addition, hydrogels can be made into injectable forms, which has attracted the interest of many researchers because they have many advantages, including the ability to fill uneven spaces in wounds, adhere to wounds, and encapsulate bioactive chemicals and cells in situ, all of which are crucial for skin tissue regeneration.

[0008] However, the industry has not yet found a medical dressing with good multiple synergistic antibacterial effects. Summary of the invention

[0009] In order to solve the above problems, the present invention provides a preparation of a curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel. The present invention first designs and prepares two nano-drugs. The natural Chinese herbal medicine curcumin is used as an antibacterial agent, and the copper ion chelates the curcumin to form nanoparticles, which are then coated with a polydopamine shell to form nanospheres. Cur Sodium nitroprusside was used as a NO donor and co-precipitated with sodium phytate to prepare nanoparticles. Then, silica was polymerized on the surface of the nanoparticles, and then dopamine was polymerized to prepare a core-shell nanodrug P. NO On this basis, carboxymethyl chitosan and oxidized hyaluronic acid were used as raw materials to prepare injectable hydrogels through Schiff base crosslinking and composite nano-drugs P cur and P NO (Gel@Cur+NO). The present invention has the following advantages: (1) Innovatively preparing nanoparticles of curcumin by metal coordination method and encapsulating polydopamine with photothermal effect to prepare nanoparticles of drug P cur . Solve the problem of poor water solubility and stability of curcumin; (2) For the first time, the nano-coprecipitation method was used to prepare sodium nitroprusside nanoparticles, and the core-shell structured nanopharmaceutical P was prepared by two-step coating with silica and polydopamine. NO .P NO It plays the dual role of NO donor and photothermal agent. (3) The hydrogel system Gel@Cur+NO organically combines the antibacterial effects of Chinese herbal medicine, NO gas therapy and photothermal antibacterial.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] The first aspect of the present invention provides a method for preparing a curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel, comprising:

[0012] Copper salt is used to chelate curcumin to form first nanoparticles, and then polydopamine is used to coat the first nanoparticles to form nanodrug P Cur ;

[0013] Sodium nitroprusside and sodium phytate were used as raw materials, and a nanometer coprecipitation method was used to prepare a second nanometer particle; and polydopamine was used to coat the second nanometer particle to prepare a nanometer drug P with a core-shell structure. NO ;

[0014] The nano drug P cur and P NO The nanocomposite dynamic cross-linked hydrogel is uniformly mixed with carboxymethyl chitosan and oxidized hyaluronic acid to form a nanocomposite dynamic cross-linked hydrogel.

[0015] In some embodiments, the mass ratio of the copper salt to curcumin is 1:2-2.5. Because curcumin has a rare β-diketone structure, it is easy to interact with metal ions to form a complex. After curcumin combines with metal ions, the structural stability is greatly improved, which enhances its ability to resist damage in the body and improves bioavailability to a certain extent. At the same time, curcumin metal complexes have multiple medicinal properties such as anti-inflammatory, antibacterial, antioxidant, and anti-tumor like curcumin. Studies have found that compared with curcumin alone, the antibacterial properties of curcumin copper complexes are significantly improved.

[0016] In some embodiments, the mass ratio of curcumin to dopamine hydrochloride is 1:1-1.1.

[0017] In some embodiments, the mass ratio of sodium phytate to sodium nitroprusside is 5:1-1.5.

[0018] In some embodiments, the mass ratio of sodium nitroprusside to dopamine hydrochloride is 1:2-2.2.

[0019] In some embodiments, the nanodrugs Pcur and P NO The mass ratio is 1:1-1.5.

[0020] In some embodiments, the mass ratio of the carboxymethyl chitosan to the oxidized hyaluronic acid is 1:2-6.

[0021] The second aspect of the present invention provides a curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel prepared by the above method.

[0022] The third aspect of the present invention provides the use of the above-mentioned curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel in the preparation of antibacterial dressings or antibacterial drugs.

[0023] The fourth aspect of the present invention provides the application of the above-mentioned curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel in drug / NO / chemodynamics / photothermal synergistic antibacterial.

[0024] Beneficial Effects of the Invention

[0025] (1) The present invention designs and develops a new copper ion-coordinated curcumin into spherical nanoparticles through the chelation reaction between curcumin (Cur) and copper ions, and then coats the dopamine shell on this basis. After the complexation, the water solubility and bioavailability of curcumin are greatly improved, which is used for effective synergistic and precise drug-photothermal antibacterial. NO NO is generated by co-doping sodium nitroprusside and sodium phytate with silica nanoparticles and PDA modification, and has a good photothermal effect under near-infrared (NIR) laser irradiation. Therefore, bacteria can be effectively killed by gas therapy in coordination with PTT. In addition, biocompatible OHA / CMC hydrogel has unique injectable self-healing properties and can be used as a promising drug and multifunctional nanoparticle delivery system. Nanocomposite hydrogels prepared by combining hydrogels with nanoparticles can release nanoparticles well. Under 808nm near-infrared laser irradiation, hydrogel-loaded nanoparticles show ideal antibacterial properties against Staphylococcus aureus and Escherichia coli through the synergistic effect of PTT and NO generation, and are verified by in vitro and in vivo antibacterial experiments. In addition to having significant antibacterial properties, nanocomposite hydrogels also have obvious advantages such as high antibacterial effect, good biosafety, convenient preparation, and low cost, and are ideal bactericidal materials for treating wound infections in vivo and in vitro. The hydrogel-loaded nanoparticles of the present invention simultaneously combine drugs, photothermal and gas therapy in one device, which helps to synergistically and accurately eliminate bacteria.

[0026] (2) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0028] Figure 1 P cur , P NO Schematic diagram of the preparation of hydrogel.

[0029] Figure 2 P cur(a) SEM image of nanoparticles (scale bar = 3.0 μm); (b) TEM image (scale bar = 100 nm); (c) P cur Dopamine shell of nanoparticles after ethanol dissolution (scale bar = 100 nm); (d) size distribution; (e) FTIR spectrum; (f) UV-visible absorption spectrum; (g) fluorescence spectrum; (h) Cur standard curve; (i) Cur maximum absorption peak and P cur The relationship between concentration.

[0030] Figure 3 Cur and P cur Optical images of the samples dissolved in water and DMSO, respectively.

[0031] Figure 4 (a) TEM image of SiO2@PA+SNP (scale bar = 200 nm); P NO (b) TEM image of nanoparticles (scale bar = 200 nm); (b) SEM image (scale bar = 5.0 μm); (d) and (e) SiO2@SNP+PA and P NO Size distribution; (f)P NO Monodisperse hollow structures; (g) FTIR spectra; (h) SiO2@SNP+PA and P NO Optical diagram in water.

[0032] Figure 5 (a) 1HNMR spectra of OHA and HA in deuterated water; (b) FTIR spectrum of hydrogel; (c) gelation time of blank hydrogel.

[0033] Figure 6 (a) Gelation time of nanocomposite hydrogel; (b) Injectability of hydrogel plus methylene blue; (c) Injectability of nanocomposite hydrogel.

[0034] Figure 7 (a) Self-healing performance photos of hydrogels with methylene blue and nanocomposite hydrogels; (b) and (d) SEM images of blank hydrogels No. 3 and 8; (c) and (e) SEM images of nanocomposite hydrogels No. 4 and 9; (f) Near-infrared radiation with power variation (10 mg / ml) and (g) corresponding images recorded by a thermal imager; (h) Near-infrared radiation with concentration variation (0.9 W / cm 2 ) and (i) corresponding images recorded by thermal imager; (j) irradiation cycle experiment of nanocomposite hydrogel.

[0035] Figure 8(a) Oscillation-frequency scanning mode of hydrogels No. 3, 4, 8, and 9; (b) time scanning mode of hydrogels No. 3 and 8; (c) time scanning mode of hydrogels No. 8 and 9; (d) oscillation-amplitude scanning mode of hydrogel No. 3; (e) oscillation-amplitude scanning mode of hydrogel No. 8; (f) oscillation-amplitude scanning mode of hydrogel No. 4; (g) oscillation-amplitude scanning mode of hydrogel No. 9.

[0036] Fig. 9 (a) Oscillation-time scanning mode of hydrogel No. 3; (b) Oscillation-time scanning mode of hydrogel No. 8; (c) Oscillation-time scanning mode of hydrogel No. 4; (d) Oscillation-time scanning mode of hydrogel No. 9; (e) Photos of colonies formed by Escherichia coli and (g) Staphylococcus aureus. (f) Corresponding bacterial survival rates of Escherichia coli and (h) Staphylococcus aureus under different treatments. DETAILED DESCRIPTION

[0037] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0038] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0039] Example 1 Preparation of Nanomedicine

[0040] 1.P cur Preparation

[0041] Dissolve copper sulfate pentahydrate (10 mg) in deionized water (20 ml), add anhydrous ethanol (20 ml) and dissolve by ultrasonication after fully dissolving; dissolve curcumin (20 mg) in dimethyl sulfoxide (2.5 ml), then add dropwise to the mixed solution of copper sulfate, stir at room temperature for 5 hours, add dopamine hydrochloride (20 mg), add ammonia water (100 μL) after 1 hour, and polymerize in the dark for 12 hours. After the reaction, centrifuge, wash with deionized water 3 times, and finally freeze-dry to obtain a black powder solid P cur (0.0367g).

[0042] 2.P NO Preparation

[0043] Sodium phytate (100 mg) was dissolved in deionized water (1.2 ml), sodium nitroprusside (SNP, 20 mg) was dissolved in deionized water (0.6 ml), the two solutions were mixed evenly and added dropwise to anhydrous ethanol (35 ml), after precipitation, tetraethyl orthosilicate (1.5 ml) and ammonia water (2 ml) were added, and the mixture was heated at 40 ° C for 6 h in the dark. After the reaction, centrifugation was performed, and the mixture was washed with anhydrous ethanol 3 times to obtain a white solid. The white solid was dispersed in anhydrous ethanol (100 ml) and ultrasonicated for 30 min, then dopamine hydrochloride (40 mg) was added, and the ultrasonication was continued for 20 min, and ethanolamine (0.48 g) was added. The mixture was reacted in the dark for 14 h. After the reaction, centrifugation was performed, the mixture was washed with anhydrous ethanol 3 times, and finally vacuum dried to obtain a gray-brown powder solid P NO (0.332g).

[0044] Example 2 Preparation of hydrogel

[0045] 1. Preparation of oxidized hyaluronic acid: Hyaluronic acid (1 g) was fully dissolved in deionized water (100 ml), and then sodium periodate (0.5 g) was added and the mixture was sealed and reacted for 5 h in a dark place. After the reaction, ethylene glycol (2 ml) was added and the reaction was continued for 2 h. The resulting solution was dialyzed against deionized water for 24 h using a dialysis bag with a molecular weight cutoff of 3500. After the dialysis was completed, the solution was concentrated by rotary evaporation and finally freeze-dried to obtain white flocculent oxidized hyaluronic acid (OHA, 0.9819 g).

[0046] 2. Preparation of blank hydrogel: Carboxymethyl chitosan was mixed evenly with PBS (7.4) at a concentration of 20 mg / ml, and then mixed with different concentrations of OHA (40 mg / ml, 60 mg / ml, 80 mg / ml, 100 mg / ml, 120 mg / ml) in equal proportions to obtain blank hydrogel.

[0047] 3. Preparation of Nanocomposite Hydrogel Gel@Cur+NO: Two Nanodrugs P cur and P NO They were first added into the carboxymethyl chitosan solution in a ratio of 1:1, and then ultrasonically dispersed, and then oxidized hyaluronic acid was added and mixed to obtain a nanocomposite hydrogel.

[0048] The numbers of the hydrogels are shown in Tables 1 and 2.

[0049] Experimental Example 1 Basic Test Characterization

[0050] Spectral analysis: UV-visible spectroscopy (UV2800S, China) was used for quantitative analysis, and the absorption spectrum was recorded in the wavelength range of 300-900 nm. Fluorescence spectra were analyzed using a fluorescence spectrometer (F97 Pro, China).

[0051] Infrared analysis: Fourier transform infrared (FTIR, Nicolet NEXUS 670, China) was used to analyze the composition of raw materials and nanoparticles. The samples were mixed with potassium bromide to form tablets, and then -1 Measurement within the range with a resolution of 4cm -1 .

[0052] Particle size and morphology analysis: Dynamic light scattering (DLS, Zetasizer Nano ZS90, UK) was used to measure the size of nanoparticles and the dispersion index. The morphology of the freeze-dried hydrogel was observed using a scanning electron microscope (SEM, TESCAN, Czech Republic). Before characterization, a layer of gold was sputtered on the hydrogel to improve the conductivity. Transmission electron microscopy (TEM, JEM 2100, Japan) and scanning electron microscopy were used to observe the P cur and P NO microscopic morphology.

[0053] Nuclear magnetic resonance analysis: 400MHz nuclear magnetic resonance (NMR) spectrometer ( 1 HNMR, JNM-ECZL400S, Japan), using D2O as solvent to obtain the HA and OHA 1 H NMR spectroscopy.

[0054] Experimental Example 2 Rheological Properties Characterization

[0055] The mechanical properties and self-healing ability of blank hydrogel and nanocomposite hydrogel were characterized by rheometer. The mechanical properties and self-healing ability of the gel were evaluated by time scanning mode, oscillation-frequency scanning mode, oscillation-amplitude scanning mode and oscillation-time scanning mode.

[0056] Experimental Example 3 Photothermal Performance Characterization

[0057] A near-infrared (NIR) laser emitter with an emission wavelength of 808 nm (Xi'an Raize Electronic Technology Co., Ltd.) was used as the light source. The temperature changes under NIR irradiation were recorded using a FLIR thermal imaging device to study the photothermal properties of the nanocomposite hydrogel. cur and P NO The nanocomposite hydrogels (0, 5 mg / ml and 15 mg / ml) were heated at 0.9 W / cm 2 The power density of the nanocomposite hydrogel (P cur and P NO ) (10 mg / ml) at different power densities (0.5, 1.0, 1.5, 2.5 W / cm 2) for 10 minutes to investigate the effect of laser power on its photothermal efficiency. The laser irradiation cooling process was repeated 5 times to evaluate the photothermal stability of the hydrogel.

[0058] Experimental Example 4 Characterization of in vitro antibacterial properties

[0059] First, the in vitro antibacterial activity of the hydrogel (Gel@Cur+NO) was determined by the plating method. The bacterial suspension was diluted to 10 8 CFU / mL, and bacterial dispersion was obtained. 150 μL of bacterial suspension was added to different concentrations of No. 1 hydrogel (P cur and P NO The antibacterial activity of the hydrogel (Gel@Cur+NO) was investigated in 150 μL of 0, 2.5, and 7.5 mg / ml of the drug. cur and P NO The content of 0, 2.5, 7.5 mg / ml) was mixed with bacterial dispersion at 0.9W / cm 2 Irradiation / no irradiation with 808nm near-infrared laser for 10min.

[0060] After different treatments, the mixed solution was incubated for 3 h at 37 ° C. After the above treatments, the obtained bacterial suspension (100 μL) was spread on Luria-Bertani (LB) agar plates and incubated at 37 ° C for 12 to 16 h, and the number of colonies was counted to determine the bacterial survival rate.

[0061] The test results of Experimental Examples 1 to 4 are as follows:

[0062] 1P cur Synthesis and characterization of

[0063] The β-diketone structural element in curcumin can isomerize into ketoenol form and chelate Cu in a mixed solution of anhydrous ethanol and aqueous solution at a ratio of 2:1. 2+ ions. P was prepared by oxidative polymerization of dopamine (DA) under weak alkaline conditions. cur PDA-assisted surface coating formed by oxidative polymerization of dopamine in weakly alkaline solution is a simple, safe, effective, and economical surface functionalization method with diverse properties, including high chemical reactivity, strong photothermal performance, and biocompatibility.

[0064] The synthesized P was observed by SEM and TEM. cur The morphology and particle size of Figure 2 As shown in a. SEM image shows P cur It is a monodisperse sphere with a smooth surface. TEM images show that P cur The P after alcohol washing was observed by TEM.cur The morphology of the dopamine shell, e.g. Figure 2 As shown in Figure c, a uniform PDA coating thickness appeared on the surface of the curcumin copper complex, which also proved that dopamine was successfully oxidatively polymerized on the surface of the curcumin copper complex to form a regular and uniform spherical core-shell structure. Figure 2 Dynamic light scattering (DLS) analysis showed that P cur The particle size of the nanoparticles is about 105.0 nm, with a small polydispersity index of 0.210, which indicates that the nanoparticles are small in size and have a relatively uniform particle size distribution. Figure 2 e is P cur FT-IR spectra of nanoparticles before and after coating. The PDA-coated nanoparticles have a wavelength of 3300-3500 cm -1 The characteristic peak at corresponds to the amine vibration in dopamine, indicating that PDA was successfully coated on the surface of the nanoparticles. cur The optical properties of P cur and UV absorption and fluorescence spectra of curcumin. Figure 2 As shown in f, at about 435nm, P cur The absorption spectrum of free Cur is similar. Determining the curcumin standard curve is helpful to analyze the relationship between curcumin concentration and absorbance. The results of the curcumin standard curve are as follows: Figure 2 The results showed that curcumin had a high concentration in the range of 0.313 to 10.000 μg mL -1 ) has a good linear relationship with the corresponding 435nm UV absorbance value, and the linear equation is y=0.1671x+0.004875(R 2 =1.000). The results show that the selected curcumin has good quality and stable UV absorption, and can be used for experimental research on the photostability of curcumin. At the same time, the maximum absorption peak and P cur The relationship between concentration, such as Figure 2 As shown in Figure 1, the results also show that P cur In the concentration range (0.62~4.45μgmL -1 ) has a good linear relationship with the corresponding ultraviolet absorbance value at about 431nm. In order to test the refractive index of Cur particles of different sizes dispersed in water through the Tyndall effect, the present invention combines Cur and P cur Dissolve in water and DMSO (eg Figure 3 Cur is soluble in DMSO but insoluble in water, while P cur Soluble in water and DMSO, which indicates that Cur and Cu 2+ The binding of P changes the polarity of Cur. curThe bioavailability of is better than Cur, because better water solubility means better bioavailability. In summary, the present invention successfully prepared P with highly enhanced stability and bioavailability by applying copper chelated curcumin to coat dopamine. cur .

[0065] 2P NO Synthesis and characterization of

[0066] Biocompatible P dispersible in ethanol was prepared by nano-coprecipitation followed by polymerization. NO Transmission electron microscopy (TEM) images show that Figure 4 As shown in (a), the prepared SiO2@PA+SNP nanoparticles have uniform morphology and size. Dynamic light scattering (DLS) ( Figure 4 The analysis in (d) shows that the particle size of SiO2@PA+SNP is about 279.2 nm, with a small polydispersity index of 0.016. Figure 4 As shown in middle e, after being coated with dopamine, P NO The particle size of the synthesized P was increased to 322.0 nm. In TEM image 4b, it can be observed that SiO2@PA+SNP was successfully coated with a dopamine shell. NO The morphology and particle size of P NO is a monodisperse sphere. Figure 4 In the middle f, the TEM image shows that by washing SiO2@PA+SNP with water, the present invention obtains a monodisperse hollow structure of SiO2@PA+SNP. Figure 4 As shown in g, the FT-IR spectrum of SiO2@PA+SNP shows that the -1 The strong and broad absorption band at the bottom is the antisymmetric stretching vibration of Si-O-Si, which proves the successful recombination of the silica shell. NO Through the refractive index of the Tyndall effect, the present invention combines SiO2@PA+SNP and P NO Dissolve in water ( Figure 4 h). SiO2@PA+SNP and P NO are easily soluble in water, which indicates that SiO2@PA+SNP and P NO All have good bioavailability.

[0067] 3 Synthesis and characterization of hydrogels

[0068] Carboxymethyl chitosan (CMC) was dissolved in PBS (pH = 7.4) at a concentration of 2% (w / v). Oxidized hyaluronic acid was dissolved in PBS (pH = 7.4) at a concentration of 2%-6% w / v. Oxidized hyaluronic acid solutions with concentrations of 2%, 3%, 4%, 5% and 6% (w / v) were prepared respectively. The 2% (w / v) CMC solution and the OHA solutions of different concentrations were vortexed for 10 seconds to obtain a uniform mixture. Five injectable hydrogels of different concentrations were obtained. Proton nuclear magnetic resonance ( 1 HNMR) spectroscopy confirmed the successful synthesis of OHA. 1 HNMR spectrum, new spectra were found at 5.18, 5.08 and 4.97 ppm ( Figure 5 a), which is attributed to the formation of aldehyde groups in OHA. In addition, the signal around 2.01 ppm corresponds to the acetyl group (-COCH3) connected to the amino group in the HA backbone. Figure 5 (b) shows the FT-IR spectrum of the injectable hydrogel. 1600 cm -1 The characteristic absorption peak at is attributed to the imine bond (RC=NR) formed by the Schiff base reaction between the aldehyde group in OHA and the amino group in CMC.

[0069] 3.1 Gelation time of injectable hydrogel

[0070] like Figure 5 As shown in Figure c, after placing the CMC / OHA mixed solution in a glass bottle tube, place it on a vortex mixer and vortex it at high speed for 10 seconds before starting the timing. Observe the glass bottle and turn it upside down every 10 seconds to observe the gel state until there is no liquid flowing in the tube and it is maintained for 1 minute, indicating that the solution has formed a hydrogel. The time required for this process is recorded as the gel time of the injectable hydrogel. In addition, it can be clearly observed that as the molar ratio of -CHO / -NH2 increases, the gel time shortens. The gel time of nanoparticles loaded is faster than that of ordinary gel time ( Figure 6 (a) This may be due to the -NH2 in dopamine, which shortens the gelation time.

[0071] Table 1 Hydrogel gelation time

[0072]

[0073] Table 2 Hydrogel formation time after loading nanoparticles

[0074]

[0075] 3.2 Injectability of injectable hydrogels

[0076] like Figure 6As shown in b and c, the precursor solution of the injectable hydrogel (CMC+OHA+methylene blue and CMC+OHA+NPs) is placed in a syringe and then slowly squeezed to observe whether the precursor solution can pass through the needle without clogging, thereby detecting whether the injectable hydrogel is injectable. The precursor solution of CMC+OHA and CMC+OHA+NPs can pass through the needle of the syringe smoothly without clogging, which is due to the shear thinning effect of the hydrogel (viscosity decreases with increasing shear stress). This experiment confirms that the hydrogel has good injectability.

[0077] 3.3 Healability of injectable hydrogels

[0078] like Figure 7 As shown in a, a macroscopic self-healing experiment is used to verify the self-healing properties of the injectable hydrogel. In the macroscopic self-healing experiment, CMC+OHA+methylene blue and CMC+OHA+NPs are taken as examples. A bromophenol blue-dyed hydrogel and a nanoparticle-loaded hydrogel are cut into two gel blocks of equal volume, and then the two hydrogel blocks of different colors are alternately combined into a mixed overall hydrogel. After the combined overall hydrogel is placed in a humid environment at room temperature for 2 hours, the movement of the bromophenol blue dye is observed, and the healed hydrogel is picked up with tweezers to observe the healing ability of the hydrogel. Figure 7 It can be clearly observed in Ⅰ-Ⅳ of a that after the two gel blocks of different colors are combined into a whole hydrogel, the boundary between the two gel blocks becomes blurred over time, indicating that there is molecular movement between adjacent gel blocks. In addition, after two injectable hydrogel blocks of different colors are combined together for 2 hours, a complete hydrogel can be formed. When picked up with tweezers, no gel block falls off (Ⅳ). The above phenomenon confirms that the nanocomposite hydrogel has good self-healing properties.

[0079] 3.4 SEM characterization of injectable hydrogels

[0080] The freeze-dried injectable hydrogel was treated with liquid nitrogen and then fractured to expose the cross section of the hydrogel. The cross section of the obtained hydrogel was sprayed with gold, and then the morphology of the hydrogel was observed by SEM. Figure 7 b) Blank hydrogel No. 3, ( Figure 7 d) No. 8 nanocomposite hydrogel and ( Figure 7 c) Blank hydrogel No. 4, ( Figure 7 (e) The morphology of the injectable hydrogel of nanocomposite hydrogel No. 9. It was found that hydrogel No. 3, nanocomposite hydrogel No. 8, hydrogel No. 4 and nanocomposite hydrogel No. 9 all have regular three-dimensional network structures.

[0081] 3.5 Photothermal properties of injectable hydrogels loaded with nanoparticles

[0082] Near-infrared laser-induced photothermal therapy has the effects of inhibiting microorganisms, increasing local microcirculatory blood flow, and reducing inflammation. Considering the photothermal properties of PDA, the temperature changes under near-infrared irradiation were recorded using FLIR thermal imaging equipment to study the photothermal properties of hydrogels loaded with nanoparticles at different concentrations. 1 ml of hydrogel was placed in a 2 mL centrifuge tube, and the temperature of the hydrogel was recorded every 30 seconds using an infrared thermal imager under 808 nm laser irradiation. First, by measuring the temperature changes of nanoparticles at different concentrations (0, 5 (P cur and P NO 7.5mg each) 15mg / mL) OHA+CMC+P cur +P NO The hydrogel was heated to a power density of 0.9 W / cm 2 Temperature rise within 10 minutes under 808nm near-infrared laser irradiation. An infrared camera (FLIR ONE) records the temperature change (ΔT) of each group every 2 minutes. Figure 7 As shown in f and g, the hydrogel with a concentration of 4 (10 mg / mL) was measured at different power densities (0.5, 1.0, 1.5, 2.5 W / cm 2 ) Temperature rise within 10 min under 808 nm near-infrared laser irradiation. An infrared camera (FLIR ONE) records the temperature change (ΔT) of each group every 2 min. Figure 7 As shown in h and i. In particular, at a concentration of 15 mg / mL, the temperature change was 12.7°C. This finding indicates that the hydrogel loaded with nanoparticles can effectively convert 808nm laser energy into local heat. The temperature of the hydrogel loaded with nanoparticles further proves that the photothermal effect is positively correlated with the laser power, showing power-dependent photothermal properties. By on / off cyclic illumination, the temperature change of the hydrogel loaded with nanoparticles was measured to study its photothermal stability. Figure 7 As shown in Figure j, the hydrogel loaded with nanoparticles showed good photothermal stability after 5 cycles, and the final temperature remained basically unchanged. In summary, the hydrogel loaded with nanoparticles has a typical photothermal effect and good photothermal stability, and can be used for photothermal therapy.

[0083] 3.6 Rheological properties of hydrogels

[0084] The blank hydrogels No. 3 and No. 4 and the nanocomposite hydrogels No. 8 and No. 9 (P cur +P NO A total of 15 mg / ml) was prepared into a hydrogel disc with a diameter of 40 mm and a height of 1000 um, and then the hydrogel disc was placed in the center of the sample stage bottom plate of the TA rheometer (2000EX) to detect relevant data. Figure 8As shown in a, when the storage modulus and loss modulus of blank hydrogels No. 3 and No. 4 and nanocomposite hydrogels No. 8 and No. 9 were tested, the fixed strain was set to 1.0%, and the angular frequency scanning range was from 0.1 rad / s to 100 rad / s. During the entire measurement process, G″ of all injectable hydrogels was less than G′, indicating that the hydrogels were in a gel state. For blank hydrogels No. 3 and No. 8 ( Figure 8 b) and No. 4 and No. 9 nanocomposite hydrogels (c) were subjected to time scanning tests, with the temperature set to 37°C, the frequency set to 1Hz, and the strain set to 1%, thereby proving the stability of No. 3 and No. 8 blank hydrogels and No. 4 and No. 9 nanocomposite hydrogels. In different time periods, G′ was greater than G″, indicating that No. 3 and No. 4 blank hydrogels and No. 8 and No. 9 nanocomposite hydrogels were always in the gel state. By setting the fixed frequency to 1Hz and the strain scanning range to γ=0.01%-500%, the No. 3 and No. 4 blank hydrogels ( Figure 8 d and e) and No. 8 and No. 9 nanocomposite hydrogels ( Figure 8 The strain at the gel-sol transition point (f and h). The storage modulus and loss modulus curves are related to a critical strain of about 200%. As the pressure increases, the G′ value suddenly drops below G″, indicating that the hydrogel network has been destroyed. In order to analyze the blank hydrogels No. 3 and No. 4 ( Fig. 9 a and c) and No. 8 and No. 9 nanocomposite hydrogels ( Fig. 9 In the test of self-healing performance (b and d), the fixed frequency was set to 1 Hz, and then the sample was scanned in a cycle time at 1% (interval time of 100 s) and 700% (interval time of 100 s) strain. The strain results of the hydrogels showed that the three-dimensional network structure of the blank hydrogels No. 3 and No. 4 and the nanocomposite hydrogels No. 8 and No. 9 could repair themselves after damage, showing good self-healing ability.

[0085] 4 Antibacterial experiment

[0086] Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive) were used as typical bacteria to evaluate the antibacterial properties of the hydrogel. The experimental equipment and samples were sterilized with a high-pressure steam sterilizer before the experiment. The plate counting method was used to detect the in vitro antibacterial effect of the nanocomposite hydrogel on the two bacteria under 808nm near-infrared irradiation. After incubating the two bacterial solutions with the nanocomposite hydrogel samples for 3 hours (37°C), the diluted bacterial solution was smeared on a solid culture dish. The colonies on the culture dish were photographed and counted, and the antibacterial rate was calculated. Fig. 9As shown in Figure eh, the nanocomposite hydrogel + near infrared exhibited strong antibacterial activity against Escherichia coli (Gram-negative bacteria) and Staphylococcus aureus (Gram-positive bacteria). The number of bacterial colonies in the PBS group decreased compared with the blank hydrogel group. This may be due to the antibacterial effect of chitosan in the hydrogel. Most notably, a satisfactory antibacterial effect was observed in the nanocomposite hydrogel + NIR group, with a reduction of nearly 99% in bacterial colonies, which may be attributed to the synergistic eradication of bacteria by photothermal and NO treatment.

[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel, characterized in that: include: Copper salt and curcumin are chelated to form first nanoparticles, and polydopamine is used to coat the first nanoparticles to form nanodrug P Cur ; Sodium nitroprusside and sodium phytate were used as raw materials, and a nanometer coprecipitation method was used to prepare a second nanometer particle; and polydopamine was used to coat the second nanometer particle to prepare a nanometer drug P with a core-shell structure. NO ; The nano drug P cur and P NO The nanocomposite dynamic cross-linked hydrogel is uniformly mixed with carboxymethyl chitosan and oxidized hyaluronic acid to form a nanocomposite dynamic cross-linked hydrogel.

2. The method for preparing the curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel according to claim 1, characterized in that: The mass ratio of the copper salt to curcumin is 1:2-2.

5.

3. The method for preparing the curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel according to claim 1, characterized in that: The mass ratio of the curcumin to dopamine hydrochloride is 1:1-1.

1.

4. The method for preparing the curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel according to claim 1, characterized in that: The mass ratio of sodium phytate to sodium nitroprusside is 5:1-1.

5.

5. The method for preparing the curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel according to claim 1, characterized in that: The mass ratio of the sodium nitroprusside to dopamine hydrochloride is 1:2-2.

2.

6. The method for preparing the curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel according to claim 1, characterized in that: The nano drug P cur and P NO The mass ratio is 1:1-1.

5.

7. The method for preparing the curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel according to claim 1, characterized in that: The mass ratio of the carboxymethyl chitosan to the oxidized hyaluronic acid is 1:2-6.

8. A curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel prepared by the method according to any one of claims 1 to 7.

9. Use of the curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel according to claim 8 in the preparation of antibacterial materials or antibacterial drugs.

10. Use of the curcumin / nitric oxide / photothermal synergistic antibacterial nano-drug composite dynamic cross-linked hydrogel according to claim 8 in drug / NO / chemodynamics / photothermal synergistic antibacterial.

Citation Information

Patent Citations

  • Electrostatic spinning membrane capable of releasing nitric oxide based on near-infrared response as well as preparation method and application of electrostatic spinning membrane

    CN111945301A

  • Double-prodrug skeleton polymer PCPt, nano-particles thereof, preparation method of nano-particles and application of nano-particles

    CN114652747A

  • Double-protein sequential delivery self-healing injectable hydrogel system and preparation method thereof

    CN118059033A

  • Method for preparing copper-mediated in situ crosslinkable hydrogel for sustained release of nitric oxide

    WO2023149692A1